Advanced stage anaplastic large cell lymphoma in children and adolescents: Results of ANHL0131, a randomized phase III trial of APO versus a modified regimen with vinblastine: A report from the children's oncology group. Issue 12 (23rd August 2014) - Alexander, Sarah; Kraveka, Jacqueline M.; Weitzman, Sheila; Lowe, Eric; Smith, Lynette; Lynch, James C.; Chang, Myron; Kinney, Marsha C.; Perkins, Sherrie L.; Laver, Joseph; Gross, Thomas G.; Weinstein, Howard
<x xml:space="preserve">Abstract</x> Background Optimal therapy for children and adolescents with advanced stage anaplastic large cell lymphoma (ALCL) is unknown. ANHL0131 examined whether a maintenance regimen including vinblastine compared to the standard APO (doxorubicin, prednisone, vincristine, methotrexate, 6‐mercaptopurine) regimen would result in superior event‐free survival. Procedure One hundred and twenty five eligible patients were enrolled. Induction was identical for both arms. Post induction patients were randomized to receive APO with vincristine every 3 weeks or a regimen that substituted vincristine with weekly vinblastine (APV). Results There was no difference between the patients randomized to the APO versus APV arms in either event free survival (EFS) or overall survival (OS) (three year EFS 74% vs. 79%, P = 0.68 and three years OS of 84% vs. 86%, P = 0.87, respectively). Patients in the APV arm required dose reduction secondary to myelosuppression and had a higher incidence of neutropenia as well as infection with neutropenia compared to those in the APO arm (P < 0.001, P = 0.019, respectively). Conclusions Treatment with weekly vinblastine instead of every three week vincristine as part of multi‐agent maintenance therapy did not result in improvement in EFS or OS. Weekly vinblastine was associated with increased toxicity. (ClinicalTrials.govIdentifier NCT00059839) Pediatr Blood Cancer 2014;61:2236–2242. © 2014 Wiley Periodicals, Inc.